Digital Literacy and Learning Motivation: Impacts on Online Learning Outcomes in Fiqh Study - Arsyad, Arsyad; Syariati, Fahma; Sukarno, Sukarno (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2023)
This study aims to investigate the effect of digital literacy skills and learning motivation on students' online learning outcomes in Fiqh subjects at Madrasah Tsanawiyah (MTs). The approach used in this study is quantitative with the data collection technique being a survey model. The sample includes 52 students, along with the corresponding teacher, from MTs Nurul Falah. The correlation data analysis is conducted using SPSS 25 software. The findings reveal a significant influence of digital literacy skills and learning motivation on online learning outcomes. Specifically, digital literacy skills account for a 90% influence on the online learning outcomes of MTs Nurul Falah students, while learning motivation accounts for an 88% influence. Moreover, the combined impact of both variables on online learning outcomes is 82%. The implications of this study underscore the necessity of enhancing digital literacy skills and nurturing learning motivation in online Fiqh courses at MTs Nurul Falah to improve students' learning outcomes. This can be accomplished through adequate training and support for students and teachers to develop digital literacy skills and learning motivation. Additionally, it is crucial to address the internal factors influencing students' digital literacy. Moreover, addressing factors such as technical issues and student motivation within the online learning environment is equally essential for optimizing online learning experiences.